(untitled) (Research, Society and Development, 2022)
Obesity is a chronic disease considered as one of the main public health problems in the world due to its damage to health, among the methods for weight loss is bariatric surgery, however, despite the success of the procedure, there is a high percentage of regain weight in the later period, preventing the achievement of its therapeutic goal. Objective: To identify and analyze the scientific evidence available in the literature about the factors that influence weight regain in patients after bariatric surgery. Methodology: This is an integrative review research, meeting the PRISMA recommendations and developed in six stages: 1) identification of the theme and formulation of the guiding question; 2) literature search; 3) categorization of studies; 4) evaluation of included studies; 5) interpretation of results; 6) synthesis of knowledge. The search was performed in Pubmed databases; Bireme; Cochrane Library; MedLine, LILACS and SciELO. Published from March 2016 to May 2022. Results: 231,369 articles were found, of which eight articles were selected that met the established criteria. The factors identified in the literature were eating habits and disorders, low adherence to physical activity, behaviors and lifestyle habits, metabolism and psychological factors. Conclusion: It is considered extremely important to identify the factors that may influence weight regain after bariatric surgery, in order to understand the reasons involved in the unfavorable outcomes and achieve multidisciplinary care in the fight against obesity, whose focus is the patient fully assisted.